MOLECULAR PROFILING OF BCR-ABL NEGATIVE MYELOPROLIFERATIVE NEOPLASMS, GOING BEYOND DRIVER MUTATIONS, SINGLE CENTER EXPERIENCE - Labachevska, Marija Popova; Stavridis, Irina Panova; Trajkova, Sanja; Ridova, Nevenka; Staninova, Marija; Jakimovska, Simona Stojanovska; Pivkova, Aleksandra; Stojanoski, Zlate; Stojkoski, Velimir (Journal of Morphological Sciences, 2023)
The classical Philadelphia chromosome-negative myeloproliferative neoplasms (MPN) comprise essential thrombocythemia (ET), primary myelofibrosis (PMF), and polycythemia vera (PV). Major complications responsible for disease-related mortality are thromboembolic and hemorrhagic events, and in a subset of MPN patients, disease transformation to secondary acute myeloid leukaemia or PMF can occur. Besides well-established driver mutations, further molecular studies, revealed novel somatic mutations i.e. non-driver mutations, whose occurrence may precede or follow the acquisition of driver mutations and can contribute in phenotypic variability, and disease progression. In order to justify these observations, we examined the mutational profile of 78 patients with MPNs using next-generation sequencing for the detection of non-driver mutations in correlation with clinical presentation. Somatic driver mutations were detected in 64 (78%) while 14 (17, 9%) were triple negative MPN cases. Most prevalent driver mutation was JAK2V617F mutation 54 (69, 2%), followed by CALR (10, 2%) and MPL in two (2, 5%). Fourteen (17, 9%) were triple negative cases. Mutations in ASXL1 gene were detected in one patient with ET and one with PMF, while mutations in TET2 gene were detected in three ET, two PV and two PMF patients, all of them  JAK2V617F positive. TP53 mutation was present in three patients, one with PV and two with ET. More than two non-driver mutations were seen in one patient with prefibrotic i.e hypercellular phase of myelofibrosis. Larger studies are needed to conclude whether the landscape of non-driver mutations differs among cohorts and how their presence affects clinical presentation. Keywords: myeloproliferative neoplasms, JAK2V617F mutation, non-driver mutations. https://doi.org/10.55302/JMS236108pl